Design and validation of the U-PlanMed questionnaire for identification of the use of medicinal plants in Babahoyo, Ecuador - Gallegos Zurita, Maritza (2016)
Introduction. The use of medicinal plants, their geographical distribution, preparation methods, forms of administration, among others, are issues that require more research and at the moment there are no validated tools or instruments to retrieve this information. Objectives. To design and validate a questionnaire that identifies the use of medicinal plants. Design. Descriptive, bservational and transversal study. Location. Rural parishes surrounding the city of Babahoyo, located in the province of Los Rios, Ecuador. Participants. Heads of households in rural communities. Methods. A questionnaire called U-PlanMed was designed and then reviewed by a multidisciplinary team of experts in order to validate its logicality and content. The survey was also administered to 30 different heads of households on two occasions separated by 20-day intervals in the months of January and February 2015. The responses obtained from the validated survey were analyzed which allowed debugging of the items while taking into consideration the frequency of response options, its item-total correlation and significant role on the items during the factorial analysis. Results. The concordance rate was 97.2% among experts regarding content validity. The reliability of the instrument was measured with Cronbach´s Alpha, with a total score of 0.8, reliability index of 0.98, coefficient correlation test re-test at 0.96. The measure of sampling adequacy from KMO and the Barlett test was 0.8. Conclusions. The U-PlanMed questionnaire is the first tool which can be used to identify the use of medicinal plants and their therapeutic applications. It has a high score of construct and content validity, and an acceptable level of consistency, both internally and externally.